Micro-structures, mineralogy and geochemistry of clay size fraction (< 2 µm) of thrust zones of western Nepal Siwaliks (Karnali area) (Journal of Nepal Geological Society, 1998)
Shear zones of the Main Dun Thrust (MDT) of the Siwaliks of western Nepal have been investigated in order to specify the deformation mechanisms and mineral transformations. The Riedel fractures and cleavage are developed. They are responsible for the scaly fabric of the fault zones and generate a "tectonic mixture" of both the Upper and Lower Siwaliks at the footwall and hangingwall of the MDT. Grain-size analysis of samples from the shear zones indicates a strong cataclastic deformation. Clay mineralogy varies significantly within the shear zone. However, the smectites abundance is higher in the shear zone than in the Upper and Lower Siwaliks and may exceed 40% of the